Assessing soil-air partitioning of PAHs and PCBs with a new fugacity passive sampler - Donald, Carey E. (Sci Total Environ, 2017)
Soil-air fluxes of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated biphenyls (PCBs) were determined using a novel application of passive samplers to measure air and soil air, which is air in close proximity and in equilibrium with soil. Existing methods to measure flux of semi-volatile compounds between soil and air require collecting samples from the top soil layer. Yet, the top soil layer is hard to define and oversampling may misrepresent the exchangeable fraction. Alternatively, modified active samplers can measure soil air in situ, but require electricity while deployed. We present a new method to measure time-weighted averages of soil air concentrations in situ using passive sampling and requiring no electricity: a box is placed over low-density polyethylene passive samplers deployed 1 cm above the soil. Passive air samplers were also co-deployed 1.5 m above the soil to measure ambient air concentrations in three U.S. locations: near a former PCB manufacturing facility in Anniston, Alabama; on a former creosoting and the current Wyckoff/Eagle Superfund site near Seattle, Washington; and near the site of a recent oil-train derailment and fire in Mosier, Oregon. Following n-hexane extraction, sampler extracts were analyzed for PAHs with gas chromatography-tandem mass spectrometry and PCBs with dual gas chromatography-electron capture detectors. PAHs were generally depositing at Anniston and Mosier sites, but volatilizing from soil in Wyckoff, the site with historically-contaminated soil. PCBs were detected most frequently at the Anniston site, although levels were lower than previous reports. Variability in concentration measurements was greater among soil air samplers than air samplers, likely due to soil heterogeneity. Environmental conditions under the novel soil air box did not substantially change soil-air partitioning behavior. This method of measuring soil air in situ will allow for understanding of source-sink dynamics at sites with recent and historical contamination, and where conventional sampling is challenging.